Preparation of a process flavoring from coconut protein hydrolysate - Vitente, Joel R.; De Leon, Sonia Y. (1985.)
Coconut protein extract was hydrolyzed with concentrated HCl solution for 6 1/2 hours. The hydrolysate mixture was filtered to remove the humins and the filtrate neutralized to pH 6 with 6N NaOH solution. The phenylalanine and methionine content of the hydrolysate was removed by treatment with activated charcoal.The protein hydrolysate was reacted with a glucose-cysteine reagent combination for one hour under reflux. It was found that the process flavoring can significantly enhance food flavor at levels of at least 1%.
Thesis (BSFT)--University of the Philippines.
Keywords: Coconut; Protein hydrolysates